Comparative Analysis of Mechanical Properties for Pointe Shoe Fabrications. Issue 6 (November 2015) - Gonzalez, Esthella; Regan, Cynthia L.; Che, Jiangning
Professional dancers incur expense when their pointe shoes are damaged by rapid abrasion and tear degradation. The mechanical properties of a typical pointe shoe fabrication were compared with potential alternatives. Individual test results varied in tensile strength, abrasion resistance, tear strength, seam strength, and seam efficiency. Eco-friendly stretch (A), stretch satin (E), gabardine (L), and plain-weave linen (M) fabrications had lower breaking loads and less abrasion resistance than the control. Elmendorf tear strength showed Fabrics E, silk chiffon (G), L, and ripstop (N) gave better results than the control. Seam strength calculation of force perpendicular to a seam showed that poplin (B), E, L, and N fabrications performed better than the control fabric. Overall results indicated that Fabrics E, L, and N were highly recommended for use in pointe shoes.